IgG4-Related Disease, the Malignancy Mimicker: Case Series from Bahrain - Majeed Haider; Fatima Haji; Osama Alalwan; Eman Aljufairi; Tejal S. Shah (Case Reports in Rheumatology)
IgG4-related disease is an evolving immune-mediated condition. The hallmark of this condition is IgG4(+) plasma cells infiltration of the affected organs accompanied by a variable degree of fibrosis and occasionally elevated serum IgG4 level. It links many conditions that were once recognized as isolated unrelated idiopathic single organ disorders (e.g., autoimmune pancreatitis, Mikulicz syndrome, and retroperitoneal fibrosis) under one umbrella. It usually presents clinically as tumor-like swelling of the involved organs that can be misdiagnosed as neoplasia. In this case series, we present four cases that were considered as neoplasia but turned out to be IgG4-related disease, we demonstrate the protean manifestations of this condition and variable organs involvement, and we share our experience in using rituximab as the steroid sparing immunosuppressant agent to control this disease.